2015
DOI: 10.1007/s12035-015-9447-0
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog Signaling Affected by Promoter Hypermethylation Induces Aberrant Gli2 Expression in Spina Bifida

Abstract: GLI2 is a key mediator of the sonic hedgehog (Shh) signaling pathway and plays an important role in neural tube development during vertebrate embryogenesis; however, the role of gli2 in human folate-related neural tube defects remains unclear. In this study, we compared methylation status and polymorphisms of gli2 between spina bifida patients and a control group to explore the underlying mechanisms related to folate deficiency in spina bifida. No single nucleotide polymorphism was found to be significantly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
(41 reference statements)
0
7
0
1
Order By: Relevance
“…Interestingly, a recent study of Petrovic et al suggests that Hedgehog signalling up-regulates SOX18 expression, which promotes migration [ 24 ]. Hedgehog signalling is known to play an important role in neural tube development [ 24 , 25 ]. Evidence for a role for SOX18 in neural tube formation is also supported by our zebrafish studies that showed strongly malformed tails with abnormal neural tube development in embryos with high levels of sox18 after injection of its mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study of Petrovic et al suggests that Hedgehog signalling up-regulates SOX18 expression, which promotes migration [ 24 ]. Hedgehog signalling is known to play an important role in neural tube development [ 24 , 25 ]. Evidence for a role for SOX18 in neural tube formation is also supported by our zebrafish studies that showed strongly malformed tails with abnormal neural tube development in embryos with high levels of sox18 after injection of its mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…It has suggested that insufficient folate intake is a cause of NTDs [33]. Impaired DNA methylation is believed to participate in this process [16,34]. Numerous investigations have indeed indicated that the aberrant methylation of miRNA around the promoter regions contributes to dysregulation of its expression [35].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have indicated that lower concentrations of folate, which in turn disturb one-carbon metabolism, during pregnancy are related to an increased risk of NTDs [13][14][15]. Previous studies by our group showed that disturbed epigenetic modifications in the context of folic acid deficiency are involved in the pathogenesis of NTDs, including DNA methylation, histone methylation and micro-RNA (miRNA) regulation [16][17][18]. Intracellular folic acid is a key factor acting as a source of adequate methyl groups for the methylation of DNA and proteins, which explains why folic acid deficiency leads to changes in cytosine methylation and histone methylation that could induce NTDs.…”
Section: Introductionmentioning
confidence: 98%
“…This indicates that in the brain tissue embryos with spina, the SHH pathway is suppressed. Data of Lu et al come to a conclusion of epigenetic silencing of GLI2 may have an important role in the development of spina bifida during embryogenesis [59]. Cladia et al suggested that TNIP1 is a new potential associated gene to spina bifida.…”
Section: Discussion On the Current Investigations On Effective Molecumentioning
confidence: 99%